The construction of an attitude scale designed to measure the attitudes of potential teachers to teaching - Wu, Chen Ching-Ching 1934- (s.n.], 1964)
The author constructed an attitude scale to measure the attitudes of potential teachers which may be useful in predicting how successful and satisfactory they will be in teaching, and to measure, indirectly, how well the potential teachers will get along with their pupils, parents and other citizens in the community.